The effects of simulated rainfall on immature population dynamics of Aedes albopictus and female oviposition - Hamady, Dieng; G. M. Saifur, Rahman; Hassan Ahmad, Abu; M. R., Che Salmah; Tomomitsu, Satho; Fumio, Miake; Michael, Boots; AbuBakar, Sazaly (Springer, 2012)
Larvae of Aedes albopictus Skuse typically inhabit natural and artificial containers. Since these larval habitats are replenished by rainfall, Ae. albopictus may experience increased loss of immature stages in areas with high levels of rainfall. In this study, we investigated the effects of rainfall and container water level on habitat quality, population density, and oviposition activity of Ae. albopictus. In field and laboratory experiments, we found that rainfall resulted in the flushing of breeding habitats. Excess rain negatively impacted larval and pupal retention, especially in small habitats. When filled with water to overflowing, container habitats were significantly repellent to ovipositing females. Taken together, these data suggest that rainfall triggers population loss of Ae. albopictus and related species through a direct detrimental effect (flushing out) and an indirect effect (habitat unsuitability and ovipositional repellency